THE ROLE OF ISIS IN THE FORMATION OF SCIENTIFIC JOURNALS AND THE HISTORIOGRAPHY OF THE HISTORY OF SCIENCE - Abdurahimov Javlonbek Bahodirjon o'g'li (Western European Studies, 2025)
This article describes one of the journals considered very important for the "history of science", the journal "Isis". It describes the history of the founding of the journal, who founded it, who contributed to this process, what articles are published in it, the scientific method of the journal and the selected directions. The purpose of the study is to reveal the role of the journal "Isis" in the formation of the history of science and how it influenced the scientific process in the history of science. The results of the study, by revealing the above issue, once again show that journals that have long been considered important in the history of science are an important source among society and scientists
Keywords: George Sarton; Isis; Osiris; History of Science